(untitled) (Al-Aasar, 2025)
Fasting constitutes a fundamental principle within the Islamic faith, serving as a practice of great significance. Specifically, fasting refers to the deliberate abstention from food and drink for a designated period. The philosophical underpinnings of fasting are elucidated in Islamic teachings, whereby it is posited that this practice cultivates virtue and piety within individuals. Notably, fasting was also mandated by Allah for previous nations that existed before the advent of the Muhammadiyah Ummah, aiming to instill piety among individuals, thereby enabling them to guard against wrongdoing through the educational and formative experiences it provides. The concept of taqwa commonly understood as a state of consciousness and fear of Allah embodies the idea that an individual should refrain from actions deemed forbidden by the Divine and endeavor to protect their soul from transgressing into sin. In the ensuing paragraphs, an examination of selected narrations concerning fasting, as recorded in Musanaf Ibn Abi Shaiba, will be presented. This review will further extrapolate relevant jurisprudential and contemporary issues arising from these narrations, contributing to a deeper understanding of the practice and its implications in both historical and modern contexts.